Resting-state EEG alterations and cognitive impairment in atrial fibrillation: insights into neural biomarkers and functional connectivity - Bao, Min-qiang; Cao, Li; Chen, Yi-nong; Gao, Guo-liang; Lu, Zhi-yong; Wang, Jie; Chen, Shuang-shuang; Sheng, Xiao-ning; Wang, Yu (Frontiers in Neurology, 2025)
AimsAtrial fibrillation (AF) is associated with cognitive decline, but the role of electroencephalography (EEG) in assessing cognitive dysfunction in AF patients is underexplored.ObjectiveThis study investigated the relationship between resting-state EEG patterns and cognitive impairment in AF patients.MethodsWe recruited 120 participants from the Affiliated Xuancheng Hospital, China (January 2023 to January 2024), categorizing them into healthy controls and AF patients. Resting-state EEG metrics, including power spectral density (PSD), functional connectivity (FC), cross-frequency coupling (CFC), and sample entropy (EnSA), were analyzed alongside the Montreal Cognitive Assessment (MoCA) scores. Mediation analysis explored EEG's role in the AF-cognitive decline relationship.ResultsAF patients had significantly lower MoCA scores. PSD analysis showed increased δ and θ and decreased α and β activity. FC was reduced in the α and β bands but increased in localized θ and γ bands. CFC analysis revealed elevated θ–β and θ–γ phase-amplitude coupling (PAC), reduced β–γ PAC, and lower EnSA. EEG metrics were significantly correlated with MoCA scores, with θ–β PAC mediating cognitive decline.ConclusionAF patients exhibit distinctive EEG changes, with θ–β PAC mediating cognitive impairment, suggesting the potential of resting-state EEG for cognitive assessment in AF patients.